Nonbacterial thrombotic endocarditis as a cause of systemic embolism - N.D. Oryshchyn (Кардіохірургія та інтервенційна кардіологія)
We presented a clinical case of the non-bacterial thrombotic endocarditis in a patient with ischemic stroke of embolic origin. Imaging methods (transthoracic and transesophageal echocardiography) showed specific features of thrombotic vegetations on mitral and aortic heart valves. Laboratory work-up (blood culture, serological examination) excluded infective endocarditis as a cause of vegetations. Diagnostic work-up with computed tomography showed lung tumor with metastatic foci in bones. Presented case demonstrates need for awareness regarding nonbacterial thrombotic endocarditis in patients with systemic embolism and in specific groups of patients (autoimmune diseases and oncology).